Servant Leadership dan Kompetensi Komunikasi:Dampaknya terhadap Kepuasan dan Kinerja Pendamping Program Keluarga Harapan (PKH) di Aceh Utara - Muhammad Sahem; Ichsan Ichsan; Naufal Bachri (Universitas Malikussaleh, 2021)
ABSTRACTThis study aims to analyze the influence of servant leadership and communication competence on the performance of Conditional Cash TransfersCoordinatorsin North Aceh with job satisfaction as an intervening variable. This study uses primary data with a total sample of 150 respondents. The sampling method used is the census method. The data analysis model used is SEM-AMOS. The results show that servant leadership does not affect job satisfaction and performance. Communication competence has a significant effect on job satisfaction and performance. Job satisfaction has a significant effect on performance. Job satisfaction does not mediate the effect of servant leadership on performance. Meanwhile, job satisfaction mediates the effect of communication competence on performance. The implications of this research is that Conditional Cash TransfersCoordinatorsin North Aceh should be able to improve the communication competency because it has the greatest influence on the Conditional Cash Transfers Coordinators performance in North Aceh Regency.Keywords: servant leadership, communication competence, job satisfaction, employeeperformance